1994
DOI: 10.1001/archinte.1994.00420120066007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patients' Compliance With Prescribed Oral and Inhaled Asthma Medications

Abstract: Comparison of medical record data with pharmacy claims data is an effective indirect measure of patients' compliance with prescribed oral theophylline and inhaled anti-inflammatory agents. Additional interventions must be pursued for patients with asthma regarding adherence to regimens for their prescribed inhaled anti-inflammatory agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(84 citation statements)
references
References 8 publications
2
81
0
1
Order By: Relevance
“…36 -38 Moreover, reduced compliance with inhaled therapy for asthma relative to orally administered therapy has been reported. 39 Additionally, inhibition of linear growth (height) in children has been observed with the administration of inhaled corticosteroids. 26,27,40,41 One potential advantage of montelukast is the ease of administering a once-daily chewable tablet.…”
Section: Discussionmentioning
confidence: 99%
“…36 -38 Moreover, reduced compliance with inhaled therapy for asthma relative to orally administered therapy has been reported. 39 Additionally, inhibition of linear growth (height) in children has been observed with the administration of inhaled corticosteroids. 26,27,40,41 One potential advantage of montelukast is the ease of administering a once-daily chewable tablet.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Newer technologies using microprocessors have shown similar results, with estimates of adherence ranging from 3% to 80%. 10 -14 There also does not seem to be a difference in adherence levels with respect to the population studied; overall estimates for adherence in both the pediatric and the adult asthma populations are ϳ50%.…”
mentioning
confidence: 86%
“…In a dose-ranging study of asthmatic patients, there was no compliance advantage to once-daily fluticasone propionate by discus compared to twice-daily dosage, but there was an efficacy disadvantage to the once-daily dosing regimen, leading the authors to recommend against the once-daily regimen (Purucker et al 2003). In a study to compare adherence rates of oral versus inhaled medications for asthma, Kelloway et al (1994) found no compliance differences between twice per day regimens versus thrice or more per day regimens for either prescribed theophylline or two inhaled anti-inflammatories. Mann et al (1992) compared adherence to twice-daily versus four-times-daily dosing of flunisolide inhalers for 16 adult asthmatics.…”
Section: Asthma and Pulmonary Diseasementioning
confidence: 99%